Pengaruh Model Pembelajaran Discovery Learning dan Minat Belajar Terhadap Hasil Belajar Fisika Peserta Didik - Juniar Rasyid; Muhammad Sidin Ali; Pariabti Palloan (Jurnal Penelitian Pendidikan IPA, 2024)
This research is a true experimental design using a 2x2 factorial design. The aim of the research is to: find out whether or not there is an influence of the application of the discovery learning learning model and interest in learning on physics learning outcomes for class XI MIPA, and diagram the interaction of the learning model and learning interest on physics learning outcomes. The independent variable in this research is the learning model, the moderator variable is interest in learning and the dependent variable is physics learning outcomes. The sample in this study was taken randomly using a simple random sampling technique which resulted in 60 people from class XI MIPA 2 and XI MIPA 3. Data from the research results were obtained by giving students interest in learning questionnaires before being taught using the learning model, and the learning outcomes tests were carried out after the students were taught using the learning model in the research. The data analysis technique used is analysis of variance (ANOVA). Based on the results of the inferential analysis, it was obtained: Fcount (9.60) > Ftable (1.30), it can be concluded that there is a significant difference between students who were taught the discovery learning learning model and students who were taught using the Inquiry Based learning model, Fcount (0. 10) < F table (1.30), it can be concluded that there is no interaction between the learning model and learning interest on physics learning outcomes.